2017
DOI: 10.3389/fnhum.2017.00212
|View full text |Cite
|
Sign up to set email alerts
|

Impairments of Motor Function While Multitasking in HIV

Abstract: Human immunodeficiency virus (HIV) became a treatable illness with the introduction of combination antiretroviral therapy (CART). As a result, patients with regular access to CART are expected to live decades with HIV. Long-term HIV infection presents unique challenges, including neurocognitive impairments defined by three major stages of HIV-associated neurocognitive disorders (HAND). The current investigation aimed to study cognitive and motor impairments in HIV using a novel multitasking paradigm. Unlike cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 54 publications
1
13
0
1
Order By: Relevance
“…Fifth, our HIV-positive group consisted of mostly non-Hispanic white males with some college education, which is not fully representative of HIV-positive persons in the United States. Sixth, prior research indicates multitasks may better detect motor impairment compared to a single motor task (i.e., finger tapping) 56 ; the Grooved Pegboard Test, however, involves the use of many complex operations and is correlated with a range of cognitive functions. 19…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, our HIV-positive group consisted of mostly non-Hispanic white males with some college education, which is not fully representative of HIV-positive persons in the United States. Sixth, prior research indicates multitasks may better detect motor impairment compared to a single motor task (i.e., finger tapping) 56 ; the Grooved Pegboard Test, however, involves the use of many complex operations and is correlated with a range of cognitive functions. 19…”
Section: Discussionmentioning
confidence: 99%
“…HIV+ subjects present a diminished motor performance at multitasking and a decreased velocity compared to the control group. This may affect the daily life and require more attention to [96]. A psychomotor slowing of HIV patients was already described in early neuropsychological studies [97], which was presumed to be from the frontostriatal origin.…”
Section: Gait/balancementioning
confidence: 88%
“…Neuropsychological testing has shown that approximately fifty percent of patients presenting HIV, in antiretroviral therapy, are afflicted by mild cognitive impairment (MCI)/HIV dementia, or other types of cognitive impairment as well as in the integrity of motor functioning, which implies that the prevalence was unaltered from the pre-to the potent antiretroviral period, although incidence of MCI had increased and HIV dementia decreased [1][2][3]. The presence -of neuropsychiatry co-morbidity in the pathophysiology of HIV compounds the suffering and detrimental prognosis of those afflicted with a complex relationship between HIV infection and psychiatric co-morbidity [4,5].…”
Section: Editorialmentioning
confidence: 99%